Determination of Antioxidant and Anti quorum Sensing Activity of Aegle marmelos Picrorrhiza kurroa and Swertia chirayita - Kamble, Pramod Ananda; Phadke, Manju (Defence Life Science Journal, 2022)
From the ancient period, humans have been fighting pathogenic microorganisms for survival purposes and in this context, man has developed antibiotics as a powerful weapon to treat various infections caused by pathogens. Nevertheless, the need to discover new antimicrobial agents is increasing at an alarming rate. This is because the microorganisms have developed various mechanisms to resist the action of antibiotics. One such mechanism is the production of biofilm. Infections caused by biofilm-forming pathogenic microorganisms are very difficult to treat, even using potent antibiotics. However, in folk medicine, many plants are found to be helpful to treat certain infectious diseases. This is because of the synthesis of a variety of bioactive compounds by plants with high medicinal value. Hence, in the present study, three different plants were used viz Aegle marmelos, Picrorrhiza kurroa, and Swertia chirayita to determine their antioxidant and anti-quorum sensing activities. According to the literature, antioxidants delay the oxidation process and nullify the effect of free radicals that cause damage and accelerate aging. Quorum sensing is the chemical way of communication between biofilm-forming microorganisms. Among the alcoholic extracts, the methanolic extract of P. kurroa showed the highest DPPH radical scavenging activity of 82.11%. All the plant extracts under investigation exhibited anti-quorum sensing activity against the standard culture of Chromobacterium violaceum MTCC 2656; however, the plant extracts of A. marmelos were found to be more potent as compared to P. kurroa and S. chirayita. Plant extracts P. kurroa and S. chirayita showed almost similar anti-quorum sensing activity. This confirms the pharmaceutical importance of plant materials of interest, which might prove to be useful to treat damage caused by free radicals and biofilm-related infections, after due consideration of clinical trials for safety issues.